THE DEVELOPMENT OF MOTIVATION RESEARCH IN EDUCATIONAL PSYCHOLOGY: THE TRANSITION FROM EARLY THEORIES TO SELF-RELATED APPROACHES - Saeed Safdari; Parviz Maftoon (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2017)
Motivation has been one of the earliest concepts of interest in general and educational psychology. Learning is mediated by individuals' reasons and choices to do something or to abstain from it. The current paper is an attempt to summarise and review the development of motivation theories, models and frameworks within educational psychology. It specifically focuses on the emergence of self-related theories in motivation research. The earlier trends and theories such as expectancy-value theories, goal theories, and attribution theories are briefly described and the influential scholars who contributed to these theoretical developments are introduced. Then, the theoretical transition to self-related theories of motivation is highlighted. A general review of self-worth, self-determination and self-efficacy theories that stemmed from the concept of self is also provided.